2020
DOI: 10.3389/fphar.2020.00702
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and Endoplasmic Reticulum Stress: A Potential Therapeutic Target for Central Nervous System Degeneration Diseases

Abstract: There are three members of the endogenous gas transmitter family. The first two are nitric oxide and carbon monoxide, and the third newly added member is hydrogen sulfide (H 2 S). They all have similar functions: relaxing blood vessels, smoothing muscles, and getting involved in the regulation of neuronal excitation, learning, and memory. The cystathionine b-synthase (CBS), 3-mercaptopyruvate sulfur transferase acts together with cysteine aminotransferase (3-MST/CAT), cystathionine g-lyase (CSE), and 3-mercapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 111 publications
(139 reference statements)
0
16
0
Order By: Relevance
“…Although the role of H 2 S that regulates ER-phagy needs to be further studied, quite recent publications have described the beneficial effect of H 2 S inhibiting ER stress, improving cellular bioenergetics and preventing autophagic arrest [70]. Therefore, it has been shown the beneficial effect of sulfide alleviating various diseases, such as central nervous system degenerative diseases [71] and disruption of the blood-spinal cord barrier [72]. Unfortunately, studies on the role of H 2 S in the regulation of ER-phagy in plants are scarce.…”
Section: Er-selective Autophagymentioning
confidence: 99%
“…Although the role of H 2 S that regulates ER-phagy needs to be further studied, quite recent publications have described the beneficial effect of H 2 S inhibiting ER stress, improving cellular bioenergetics and preventing autophagic arrest [70]. Therefore, it has been shown the beneficial effect of sulfide alleviating various diseases, such as central nervous system degenerative diseases [71] and disruption of the blood-spinal cord barrier [72]. Unfortunately, studies on the role of H 2 S in the regulation of ER-phagy in plants are scarce.…”
Section: Er-selective Autophagymentioning
confidence: 99%
“…Beyond the previously described signals acting on CAC, it has been demonstrated that CAC is an H 2 S sensor. H 2 S is one of the endogenous gas transmitters (NO, CO and H 2 S), which is produced by several enzymatic pathways, two of them being mitochondrial [ 125 , 126 , 127 , 128 , 129 ]. H 2 S exerts its action on CAC interacting with the “crucial” Cys-136 and Cys-155 couple.…”
Section: Cac As a Redox Sensormentioning
confidence: 99%
“…H 2 S regulates ERS and shows a broad variety of cytoprotective and physiological functions in CNS degenerative diseases. The neuroprotective effect of H 2 S for ERS has an important role in various CNS diseases as well as Parkinson’s disease, depression disorders, and Alzheimer’s disease [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S donors, then, could represent a potential therapeutic opportunity for the treatment of COVID-19 [ 103 ]. The alteration of H 2 S levels in COVID-19 represent further evidence of the need to regulate the homeostasis of this gasotransmitter, considering that the alteration of H 2 S levels has an important role in several diseases [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Introductionmentioning
confidence: 99%